Managerial Economic Strategies In Improving Micro Business - Nurcahyo Agung Pambudhi; Guntur Eko Saputro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Micro, small and medium enterprises or better known as MSMEs. Currently its existence is a priority for the government because it is considered capable of significantly developing the national economy in Indonesia. In developing the national economy in Indonesia, the priority is Micro, Small and Medium Enterprises (MSMEs). MSMEs are the backbone of the people's economic system to reduce the problem of poverty and their development is able to expand the economic base and can make a significant contribution to improving the regional economy and national economic resilience. This research is a qualitative descriptive study using a library research approach. The data source in this research is a secondary data source. Data collection techniques using keyword searches, subject searches and the latest scientific articles. The results of the research found that: The development of MSMEs is not free from challenges that urgently need to find solutions, including human resource, managerial, monitoring and evaluation, trust and capital issues so that they can improve and develop MSMEs in order to increase national economic resilience.